Improving coffee productivity in Ethiopia: The impact of a coffee tree rejuvenation training program on stumping - Abate, Gashaw T.; Bernard, Tanguy; Regassa, Mekdim D.; Minten, Bart (International Food Policy Research Institute, 2021)
Coffee is Ethiopia’s most important export commodity, cultivated by over 6 million smallholder farmers in the country, and accounting for about one-third of the country’s commodity exports. While coffee production has increased over the last decade, coffee yields are low and several constraints to improved productivity remain. With two-three decades old and low-yielding coffee trees in particular, the sector cannot attain its full potential. In this paper, we assess the short-term impact of a coffee tree rejuvenation training program in Sidama on adoption rate and intensity of stumping – currently the best practice to revitalize ageing coffee trees and substantially improve their productivity. Using baseline and follow-up data and a difference-in-difference approach, we find that the adoption rate and intensity of stumping has increased by about threefold during the first year of the rejuvenation training intervention.